2007
DOI: 10.1093/europace/eum021
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of rate adaptive pacing with single or dual sensors to health-related quality of life

Abstract: Pacemaker implantation strongly improves QoL, but neither single- nor dual- sensor-driven pacing offered additional improvement in QoL during the initial 8 months after the first PM implant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 27 publications
2
15
0
1
Order By: Relevance
“…In this study there was no association between Vp and HRQoL after pacemaker implantation. Hemel et al [22] came to similar conclusions in their study, which demonstrated no association between percentage of QRS complexes generated at the preset stimulation rate (DDDR mode) and HRQoL. Interpretation of the results of above clinical trials regarding lack of impact of percentage of Vp on HRQoL is only seemingly straight-forward.…”
Section: Discussionmentioning
confidence: 53%
“…In this study there was no association between Vp and HRQoL after pacemaker implantation. Hemel et al [22] came to similar conclusions in their study, which demonstrated no association between percentage of QRS complexes generated at the preset stimulation rate (DDDR mode) and HRQoL. Interpretation of the results of above clinical trials regarding lack of impact of percentage of Vp on HRQoL is only seemingly straight-forward.…”
Section: Discussionmentioning
confidence: 53%
“…However, there is evidence to suggest that MV sensor driven rate-adaptive pacing may provide a more physiologic heart rate response than accelerometer alone [10]. Whether this improved heart rate profile provided by MV sensor driven pacing translates into a greater functional capacity is ill-defined and previous studies evaluating the benefit of rate-modulated pacing on endpoints such as quality of life have been mixed [8,29,30]. Several issues may contribute to the varied outcomes of previous trials.…”
Section: Discussionmentioning
confidence: 99%
“…This pilot study provides information on the patho‐physiological effects of different pacing rates on regional and global MBF in patients with normal left ventricular (LV) function. Insight toward possible rate‐dependent changes of regional MBF is of importance to understand one of the reasons of the variable outcome of rate‐adaptive pacing introduced to increase heart rate corresponding to metabolic demand and level of exercise 9 . To explore rate‐dependent changes of regional MBF, we examined the effects of variation of atrial or ventricular pacing rates on quantitative global and regional MBF in patients with normal LV contraction using H 2 15 O positron emission tomography (PET).…”
Section: Introductionmentioning
confidence: 99%